Editorial - Nuri Balta (Journal of Research in Science, Mathematics and Technology Education, 2018)
We are pleased to publish the first issue of the Journal of Research in Science, Mathematics and Technology Education (JRSMTE). JRSMTE is an excellent example of international collaboration of researchers. It is born with the cooperation of 32 scholars from 22 different countries. Establishing the editorial board took about 6 months. The quality of a journal is in a way reflective of the quality of its editors and editorial board, and its members. That is why, we generally invited and accepted the predominant scholars as editors around the world.